An investigation of ostrich eggshell bead size variability and the introduction of cup morphology - Wells, Nicola (Department of Archaeology, 2026)
Ostrich eggshell beads are valued not only as decorations but also as important social and cultural symbols by those who create and use them. Originating in the Middle Stone Age (MSA), OES beads are still produced by several African communities. Early investigations of OES beads recovered from archaeological sites provided only rudimentary descriptions. Subsequent research has investigated more advanced aspects, including methods of bead production, patterns of use wear and isotopic provenancing. Despite many advances over the years, studies focusing on measurements continue to aid in the interpretation of the findings from these new and novel methodologies. This thesis follows the tradition of earlier metric studies by investigating variability in bead diameter, aperture diameter and cup diameter measurements, as well as cup percentage measurements in OES bead assemblages from sites along South Africa's western, south-western and southern coasts. Furthermore, the study examines variations in the shapes of bead cups. The results of the study show that there was a significant increase in average bead diameter size and variability, during the last 2 000 years. This provides support for the idea that migrant herders introduced large beads to the region and that their beads could be separated from the much smaller beads made by local hunter-gatherers by referring to a threshold of “boundary” bead size. However, a definitive bead size that allows for a complete separation of OES bead assemblages made by the two groups, could not be identified by this study. Before 2 000 BP, size changes in OES beads were more likely influenced by environmental factors rather than human migrations. A greater number of larger beads were made during periods when resources were abundant, while more smaller beads were made when resources were scarce. However, this pattern is more defined along the western and south-western coasts compared to the southern coast. Technical, functional and cultural factors influenced the size of bead apertures and the shapes of cups. Late Holocene social transformations introduced a large amount of variability, while improvements in manufacturing precision and standardisation of bead sizes accompanied the introduction of microlithic stone tool technologies.